2022
DOI: 10.1002/fsn3.2771
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa flour as a skim milk powder replacer in concentrated yogurts: Effect on their physicochemical, technological, and sensory properties

Abstract: Milk standardization with solids (i.e., nonfat milk solids, MSNF) for yogurt manufacture is traditionally achieved by the addition of skim milk powder (SMP). However, the addition of SMP to milk‐based yogurt increases lactose content and decreases both protein content and gel firmness. Thus, in this work, quinoa flour (QF; 0%, 25%, 50%, 75%, and 100% w/w) was used to replace SMP in concentrated yogurt. The physicochemical, textural, and sensory properties and microstructure of the yogurt were evaluated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…Similar results have been reported by other researchers for non‐dairy products (Arabi et al, 2018 ). According to Alkobeisi et al ( 2022 ), quinoa starch gelatinizes during thermal processing of milk and absorbs water, leading to an improvement in the viscosity of the final products.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported by other researchers for non‐dairy products (Arabi et al, 2018 ). According to Alkobeisi et al ( 2022 ), quinoa starch gelatinizes during thermal processing of milk and absorbs water, leading to an improvement in the viscosity of the final products.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel with our results regarding the skimmed-milk-based sample, they found that the pH of skimmed milk during fermentation was not lowered sufficiently when the millet was added. The long fermentation time in the skimmed milk-MM sample is mainly associated with a higher protein content than other samples, which resulted in a higher buffering capacity [33]. In contrast, the shorter fermentation time for buttermilk-MM may be because the initial acidity of this sample before fermentation was the highest.…”
Section: Discussionmentioning
confidence: 96%